Problematika Pendidikan pada Jenjang Sekolah Dasar (Kenakalan Siswa dan Kemalasan Siswa) - Maribot, Amel; Raihani, Saula; Cibro, Desnita Satriani; Pulungan, Winda Mora (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
In the learning process, elementary school (SD) students face various challenges such as social problems in the form of bullying which can very clearly affect students' enthusiasm for learning, and student delinquency which is caused by family and environmental factors both at school and around the home. As an effort to resolve this challenge, which if left unchecked will become a big problem and will carry over to school students to higher education. Teachers and schools need to make efforts to handle this, such as holding consultations for students who have problems, giving punishments that deter students from making these mistakes. And teachers and schools collaborate between the school and the students' parents.